1992
DOI: 10.1136/adc.67.1_spec_no.5
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone increases plasma amino acid concentrations in bronchopulmonary dysplasia.

Abstract: Nine ventilated low birthweight babies were treated with dexamethasone (0-6 mg/kg/day). Appreciable suppression of weight gain was accompanied by uraemia and significant increases in the concentration of ali amino acids except phenylalanine, tyrosine, threonine, and glutamate. Ornithine, citrulline, alanine, glutamine, and cystine concentrations increased threefold or more. The findings could not be explained by changes in dietary intake and presumably reflect pronounced catabolism, though the effects of dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Infants receiving dexamethasone also have elevated blood urea nitrogen and reduced nitrogen re tention associated with reduced growth and lean body mass [7], Recently, leucine kinetic studies in dexamethasone-treated infants [10] and piglets [11] have demonstrated that our observed reductions in lean body mass are likely due to elevations in protein catabolism rather than reductions in protein anabolism. In infants, protein turnover was elevated dur ing high doses (0.35 mg/kg/day) of dexameth asone [10] which were lower than those re ceived by the piglets and in other infant stud ies [6,7]. Administration of dexamethasone (5 mg/kg/day) to piglets at doses ten times in excess of those given to human infants in duces protein catabolism in parallel to that observed in infants [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants receiving dexamethasone also have elevated blood urea nitrogen and reduced nitrogen re tention associated with reduced growth and lean body mass [7], Recently, leucine kinetic studies in dexamethasone-treated infants [10] and piglets [11] have demonstrated that our observed reductions in lean body mass are likely due to elevations in protein catabolism rather than reductions in protein anabolism. In infants, protein turnover was elevated dur ing high doses (0.35 mg/kg/day) of dexameth asone [10] which were lower than those re ceived by the piglets and in other infant stud ies [6,7]. Administration of dexamethasone (5 mg/kg/day) to piglets at doses ten times in excess of those given to human infants in duces protein catabolism in parallel to that observed in infants [11].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term benefits of steroids in reducing morbidity in this clinical population arc not as clearly defined [4,5]. While dexametha sone is now common therapy for premature infants with chronic lung disease [3], doses of this steroid which are used to improve lung function arc also capable of reducing neonatal growth [6][7][8][9], Furthermore, dexaméthasone therapy induces muscle protein catabolism [7,10] as indicated biochemically in infants re ceiving dexamethasone and by elevated leu cine turnover and oxidation in piglets using l3C-lcucine tracers [11]. However, the extent of protein catabolism and the effect on depo sition of whole body lean mass has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental changes in the effect of dexamethasone on amino acid transport and metabolism have been previously noted. In newborn babies (15,20) and in newborn rats (8), dexamethasone infusion causes a marked increase in the plasma concentration of several amino acids, glutamine and alanine included, whereas in adult men (21), it causes no significant concentration changes, with the exception of a small increase in alanine. In contrast to hepatocytes isolated from adult rats, fetal rat hepatocytes do not respond to dexamethasone with an increase in system A-mediated transport (9).…”
Section: Fetal Arterial Concentrations and Umbilical And Hepatic Upmentioning
confidence: 99%
“…All infants gained weight before and during the study period; however, the average weight gain before steroid initiation was greater than that observed during steroid therapy. This finding could be due not only to a dehydration effect, but to an increase in protein catabolism, resulting in the breakdown of structural protein [24][25][26].…”
Section: Discussionmentioning
confidence: 84%